Uptake and stability of DNA nanostructures in cells: a cross-sectional overview of the current state of the art. Issue 6 (25th January 2023) - Mathur, Divita; Galvan, Angelica Rose; Green, Christopher M.; Liu, Kevin; Medintz, Igor L.
Abstract : Schematic representation of the effect of nucleases on the stability of a DNA structure, which is shown to break along the edges. This article reviews the uptake of DNA nanostructures into mammalian cells for therapeutic interventions. Abstract : The physical and chemical properties of synthetic DNA have transformed this prototypical biopolymer into a versatile nanoscale building block material in the form of DNA nanotechnology. DNA nanotechnology is, in turn, providing unprecedented precision bioengineering for numerous biomedical applications at the nanoscale including next generation immune-modulatory materials, vectors for targeted delivery of nucleic acids, drugs, and contrast agents, intelligent sensors for diagnostics, and theranostics, which combines several of these functionalities into a single construct. Assembling a DNA nanostructure to be programmed with a specific number of targeting moieties on its surface to imbue it with concomitant cellular uptake and retention capabilities along with carrying a specific therapeutic dose is now eminently feasible due to the extraordinary self-assembling properties and high formation efficiency of these materials. However, what remains still only partially addressed is how exactly this class of materials is taken up into cells in both the native state and as targeted or chemically facilitated, along with how stable they are inside the cellular cytosol and other cellular organelles. In this minireview, we summarize what is currently reported in the literature about how (i) DNA nanostructures are taken up into cells along with (ii) what is understood about their subsequent stability in the complex multi-organelle environment of the cellular milieu along with biological fluids in general. This allows us to highlight the many challenges that still remain to overcome in understanding DNA nanostructure–cellular interactions in order to fully translate these exciting new materials.